2022
DOI: 10.3390/cancers14112626
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Blood-Based Biomarkers for Predicting Immunotherapy Response in NSCLC

Abstract: Immunotherapy with Immune Checkpoint Inhibitors (ICIs) has demonstrated a profitable performance for Non-Small Cell Lung Cancer (NSCLC) cancer treatment in some patients; however, there is still a percentage of patients in whom immunotherapy does not provide the desired results regarding beneficial outcomes. Therefore, obtaining predictive biomarkers for ICI response will improve the treatment management in clinical practice. In this sense, liquid biopsy appears as a promising method to obtain samples in a min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 101 publications
0
5
0
Order By: Relevance
“…Multiple biomarkers obtained from liquid biopsy, including soluble PD-L1, circulating immune cells, circulating noncoding RNA, peripheral blood cytokines, and circulating tumor DNA, could predict the responses to ICIs at baseline and monitor changes in the TIME during the treatment. 25 Previous research indicated that SECTM1 could be detected in serum from melanoma patients but not normal donors, 13 we also examined the predictive value of circulating SECTM1 and uncovered that circulating SECTM1 was positively correlated with tumor-expressed SECTM1 and could effectively predict the responses to ICIs. These data raised the possibility that SECTM1 could be used as serum biomarker.…”
Section: Discussionmentioning
confidence: 93%
“…Multiple biomarkers obtained from liquid biopsy, including soluble PD-L1, circulating immune cells, circulating noncoding RNA, peripheral blood cytokines, and circulating tumor DNA, could predict the responses to ICIs at baseline and monitor changes in the TIME during the treatment. 25 Previous research indicated that SECTM1 could be detected in serum from melanoma patients but not normal donors, 13 we also examined the predictive value of circulating SECTM1 and uncovered that circulating SECTM1 was positively correlated with tumor-expressed SECTM1 and could effectively predict the responses to ICIs. These data raised the possibility that SECTM1 could be used as serum biomarker.…”
Section: Discussionmentioning
confidence: 93%
“…Yu and his colleagues disclosed CD273 was upregulated in LUAD, and was correlated with lymph node metastasis ( 48 ). Likewise, accumulating studies have indicated the close association between the efficacy of immunotherapy and the CD274 expression ( 49 ). VTCN1, also named B7-H4, belongs to the co-stimulatory B7 family molecules and is associated with a poor prognosis in multiple cancer types ( 50 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is vital to select the exact patients for immunotherapy. Many new biomarkers, such as tumorous mutations, circulating tumor DNA and gut microbiota, are emerging [ 10 , 11 ]. Among them, non-coding RNAs, including miRNA, lncRNA and circRNA, have intrigued numerous researchers.…”
Section: Introductionmentioning
confidence: 99%